2012
DOI: 10.1186/1471-2164-13-617
|View full text |Cite
|
Sign up to set email alerts
|

The Schistosoma mansoni phylome: using evolutionary genomics to gain insight into a parasite’s biology

Abstract: BackgroundSchistosoma mansoni is one of the causative agents of schistosomiasis, a neglected tropical disease that affects about 237 million people worldwide. Despite recent efforts, we still lack a general understanding of the relevant host-parasite interactions, and the possible treatments are limited by the emergence of resistant strains and the absence of a vaccine. The S. mansoni genome was completely sequenced and still under continuous annotation. Nevertheless, more than 45% of the encoded proteins rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 94 publications
0
28
0
Order By: Relevance
“…Indeed, Silva et al [72], using a phylogenomic approach to identify lineage-specific gene duplications, concluded that expansion of the FucT gene family was among the most significant to have occurred in S. mansoni . In general, the downstream consequences for duplicated genes include nonfunctionalization (collection of degenerative mutations), neofunctionalization (attainment of a new function), and subfunctionalization (partitioning of the original function between duplicate genes) (reviewed by Hurles [73]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Silva et al [72], using a phylogenomic approach to identify lineage-specific gene duplications, concluded that expansion of the FucT gene family was among the most significant to have occurred in S. mansoni . In general, the downstream consequences for duplicated genes include nonfunctionalization (collection of degenerative mutations), neofunctionalization (attainment of a new function), and subfunctionalization (partitioning of the original function between duplicate genes) (reviewed by Hurles [73]).…”
Section: Resultsmentioning
confidence: 99%
“…Our search yielded 15 complete genes, including seven α3-FucTs, six α6-FucTs and two protein O-FucTs. Why schistosomes encode such a large number of FucT homologs remains unclear, however it is thought that such duplicative expansions are an adaptive response to the parasitic lifestyle and imply important roles for these genes in schistosome development and immunobiology [72]. Notably, this level of redundancy also exists in the non-parasitic nematode Caenorhabditis (see Figure 5; Table S5), which Oriol et al [36] attributes to the evolutionary selection of fucosylation over sialylation as a means of terminating glycosylation.…”
Section: Resultsmentioning
confidence: 99%
“…We used a visual analytics approach to integrate these data types and to identify orthologous pairs of protein sequences with a protein length of 184 aa USP in S. mansoni (Smp_076400) and S. japonicum (Locus Tag: Sjp_0058490; UniProt ID: Q86DW2). Gene synteny, obtained from SchistoDB49 and evolutionary genomics analysis called the S. mansoni phylome,63 indicated that an ortholog (Sha_107834) is encoded in the S. haematobium genome. Thus, the genomes of the three major human schistosomiasis parasites encode the 184 aa USP.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenomics has been applied to schistosomes so as to place their proteomes into a broad evolutionary context with other parasitic and reference species as a novel approach to better understand their biology, particularly their interactions with their hosts [23]. Using this broad approach, insights into a wide range of features associated with host-parasite interactions were obtained with the primary aim of discovering new vaccine or drug targets.…”
Section: A Systems Approach To Schistosome Biologymentioning
confidence: 99%